2015
DOI: 10.1021/nn507408m
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Optical Probing of Highly Extended, Ultrathin Graphene Nanoribbons in Carbon Nanotubes

Abstract: Nanotemplated growth of graphene nanoribbons (GNRs) inside carbon nanotubes is a promising mean to fabricate ultrathin ribbons with desired side edge configuration. We report the optical properties of the GNRs formed in single-wall carbon nanotubes. When coronene is used as the precursor, extended GNRs are grown via a high-temperature annealing at 700 °C. Their optical responses are probed through the diazonium-based side-wall functionalization, which effectively suppresses the excitonic absorption peaks of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 38 publications
2
33
0
Order By: Relevance
“…30a). 280 The excitonic absorption peaks of the nanotubes were efficiently suppressed, revealing the optical transitions of the coronenebased GNRs at 1.5 and 3.4 eV. The structures of the resulting GNRs were dependent on the starting monomer.…”
Section: Synthesis Of Gnrs Confined In Carbon Nanotubesmentioning
confidence: 97%
“…30a). 280 The excitonic absorption peaks of the nanotubes were efficiently suppressed, revealing the optical transitions of the coronenebased GNRs at 1.5 and 3.4 eV. The structures of the resulting GNRs were dependent on the starting monomer.…”
Section: Synthesis Of Gnrs Confined In Carbon Nanotubesmentioning
confidence: 97%
“…There are, however, some unsavory points corresponding to reproducibility and yield of graphene liquid cells because of vulnerability of low-crystalline graphene sheets. It is important to utilize high-quality graphene to ease the fabrication of the graphene liquid cells as well as of graphene nano-ribbons [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Such differences suggest that the lengths of the formed graphene ribbons are different, depending on the annealing temperature. It has been reported that higher annealing temperature will induce further polymerization of coronene molecules into longer GRNs when coronene is used as the precursor into the nanotubes . According to early literatures, the peak profile of the encapsulated GNRAs annealed at 300 °C and 400 °C shows some similarities with the spectrum of terrylene, while the spectra of the samples annealed above 400 °C are similar to the spectrum of quaterrylene.…”
Section: Resultsmentioning
confidence: 99%
“…The modification of the GNRs width and edge structure holds great prospects in a wide range of devices applications. It has been reported that fusion of precursor molecules filled in a template such as carbon nanotubes is an efficient way to fabricate GNRs, which is a promising way to synthesize GNRs with different sizes and edge configuration. Very recently, Talyzin et al filled polycyclic aromatic hydrocarbons (PAHs) molecules into carbon nanotubes and found that GNRs can be formed inside the tubes by polymerization of PAH molecules .…”
Section: Introductionmentioning
confidence: 99%